Wakaf Uang dan Pengaruhnya terhadap Program Pengentasan Kemiskinan di Indonesia - M. Nur Rianto Al Arif (JURNAL INDO-ISLAMIKA, 2012)
Cash waqf has played a significant role in economics as one of the new Islamic fiscal instruments. Cash waqf has two functions. First, it functions as a facility for the purpose of worship and secondly, it constitutes means as to achieve social welfare. The return of cash waqf management can be used as an instrument for poverty alleviation program through social security system. As a social security system, cash waqf will contribute to the government’s alleviation program which focuses on community empowerment. This paper discusses the role of cash waqf in alleviating poverty which recently has become government program. It observes how the income of the cash waqf is distributed and how it gives an impact on the poverty alleviation in Indonesia. Deploying bibliographical and empirical investigation, this paper argues that the cash waqf has significant role in financial empowerment of the society.